1989
DOI: 10.1007/bf00309768
|View full text |Cite
|
Sign up to set email alerts
|

Origin of somatic cells and histogenesis in the primordial gonad of the Japanese tree frog Rhacophorus arboreus

Abstract: Gonadal development in Rhacophorus arboreus, a sexually semidifferentiated type of tree frog, was observed by means of the electron microscope, and cell proliferation kinetics were examined autoradiographically. The genital ridge consisted of coelomic epithelial cells and primordial germ cells. The gonadal medulla was formed by the segregation of epithelial cells within the primordial gonad. Thereafter, the medullary cell mass was well developed and oogenesis began in the gonadal cortex, irrespective of geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…At 21°C tadpoles completed metamorphosis in 9 weeks, when their ovaries were at Stage V (according to our study), which is very similar to the situation in Rana temporaria. The same relation between the ovary and somatic development was described for Bombina orientalis (Lopez, 1989) and the Japanese tree frog Rhacophorus arboreus (Tanimura and Iwasawa, 1989).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…At 21°C tadpoles completed metamorphosis in 9 weeks, when their ovaries were at Stage V (according to our study), which is very similar to the situation in Rana temporaria. The same relation between the ovary and somatic development was described for Bombina orientalis (Lopez, 1989) and the Japanese tree frog Rhacophorus arboreus (Tanimura and Iwasawa, 1989).…”
Section: Discussionmentioning
confidence: 56%
“…Our knowledge about ovary differentiation in anuran amphibians is limited to the following genera and families: Rana (Ranidae) (Witschi, 1929;Cheng, 1932;Grant, 1953;Kemp, 1953;Mizell, 1964;Jør-gensen, 1981;Wang and Hsu, 1974;Ogielska, 1990;Wagner, 1990, 1993;Ogielska 1990, 1993;Falconi et al, 2001); Bufo (Bufonidae) (Tanimura and Iwasawa, 1987;Jørgensen 1973Jørgensen , 1974Jørgensen , 1984Billeter and Jorgensen, 1976), Xenopus (Pipidae) (Al-Mukhtar and Webb, 1971;Dumont, 1972;Kress and Spornitz, 1972;Coggins, 1973;Iwasawa and Yamaguchi, 1984); Bombina (Discoglossidae) (Lopez, 1989); Rhacophorus (Rhacophoridae) (Tanimura and Iwasawa, 1989).…”
mentioning
confidence: 98%
“…Pseudis platensis exhibits a pattern of gonadal differentiation in which the testes differentiate initially into ovaries irrespective of the genetic sex, and later the ovaries in genetic males transform into testes (Gramapurohit et al, 2000). The onset of testicular formation in P. platensis is associated with the degeneration of oocytes at the beginning of metamorphosis, as in Rhacophorus arboreus (Tanimura and Iwasawa, 1989). In other species, such as Lithobates catesbeianus (Chavadej et al, 2000), Clinotarsus curtipes, and Pelophylax lessonae (Gramapurohit et al, 2000), ovarian degeneration and testicular development occurs earlier.…”
Section: Gonad Differentiationmentioning
confidence: 97%
“…This layer is also lined by an uninterrupted basal lamina along the margin facing the primary gonadal cavity. The presence of basal lamina on the margin of the cortex and medulla facing the gonadal cavity was also described by Merchant-Larios & Villalpando (1981) and Tanimura & Iwasawa (1989). These Authors, however, observed interruptions in the basal lamina between the lamina that lined the cortex and the section that lined the common coelomic epithelium as well as in the basal lamina around the medulla, and they did not observe a lamina lining the follicles surrounding the diplotenic oocytes.…”
mentioning
confidence: 71%
“…Merchant-Larios (1979), Merchant-Larios & Villalpando (1981), Iwasawa & Yamaguchi (1984), and Tanimura & Iwasawa (1988, 1989 stated that other somatic components of the genital buds originated in the soma of the cortex. Our observations do not yield enough information to formulate hypotheses on the origin of medullary cells, while the extragonadic origin suggested by Witschi (1914bWitschi ( , 1957 and Vannini (1942aVannini ( , 1950Vannini ( , 1956) is not to be discarded.…”
mentioning
confidence: 99%